Efek Pendidikan Kewirausahaan terhadap Sikap Wirausaha Mahasiswa Pendidikan Biologi : Moderasi Self Efficacy - Baiq Mirawati; Subagio Subagio (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to determine the effect of entrepreneurship education with self-efficacy moderation on student entrepreneurial attitudes. This study is a descriptive exploratory study with 35 biology education students as subjects. The research instrument used was a closed questionnaire with degraded attitude answers according to the Likert scale and had been validated by experts. Analysis of the research data used is descriptive statistics and inferential statistics with the Moderate Regression Analysis (MRA) test at a significance level of 5%. The results of the study show that: 1) student perceptions of entrepreneurship education have an average of 3.15 in the good category, self-efficacy is 3.12 in the good category, and entrepreneurial attitude is 3.06 in the good category; 2) there is an effect of entrepreneurship education with self-efficacy moderation on student entrepreneurial attitudes with an F value of 93.109, and a significance value of 0.000 which is less than the alpha testing value of 0.05 (> 0.05); and 3) entrepreneurship education with self-efficacy moderation influences student entrepreneurial attitudes by 73.8%, and the rest is influenced by variables or other factors.